Context and teacher requirements to develop students’ multiple intelligences in the classroom. - Real Castelao, Sara; Solís García, Patricia (SATHIRI, 2019)
The context and the teaching profile have been key elements in the development of the theory of multiple Intelligences but, nevertheless, since the formulation of this theory they have received less importance in the teachers educational trainings than the conceptual aspects and their applications. For this reason the aim of this work is to emphasize the importance of these elements, which should be included in teaching training. To this end, the main documentary archives of the theory written by Howard Gardner and other key authors in the application of the theory were reviewed. This review resulted in reasoning and reflection on the need for a change in the school context, with a pluralist vision centered on the student. In addition, a description of the teacher profile needed to develop the theory successfully in the classroom was made, based on certain requirements, such as deep knowledge of theory and students, teamwork, management of new technologies or critical reflection, among others. The research was concluded by summarizing the concepts addressed and highlighting their importance to effectively develop the applications of the “Multiple Intelligences Theory”, and the need to include these aspects in the trainings that are made by schools which want to develop this theory.
Keywords: multiple intelligences; school context; teacher profile